Implementación de Servicios de media Streaming sobre IPV6 en Protocolos HTTP y RTP en una Red Académica de Tecnología Avanzada - Ferro Escobar, Roberto; Martinez, Carlos; Cortés, Ernesto (Cadernos de Informática, 2011)
Inside at the group in Electronics Research Laboratory and the Distrital University networks, we implement a prototype of Streaming Service on Operating Systems Fedora 13 with VLC on the Net Programme for Research and Technology from the Distrital University “RITA-UD” over IPv6. Tests were carried Streaming media service on the RTP and HTTP protocols